ANALISIS PENGARUH FAKTOR MIKRO EKONOMI TERHADAP RISIKO INVESTASI SAHAM PADA SEKTOR INDUSTRI MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Made Santana Putra Ni Putu Sri; I Gede Rihayana; Putu Agus Eka Rismawan; Bagus Nyoman Kusuma Putra (Universitas Panji Sakti, 2019)
The Indonesian Capital Market have an important role in mobilization of founds for national development. The capability of Indonesian Capital Market in mobilizing funds has become an important container besides banking to provide funds through the sale of shares and bonds. The counting of return and risk is two important things in any capital or fund to be invested. Investment risk generally be affected bymicro and macro factors. The purpose of this research is to analyze how the effect of financial leverage, operating leverage and company liquidity simultaneously and partially to share investment risk on the food and beverage industry in indonesia stock exchange period 2013-2017. The result of this research were the variable of economic conditions, interest rate, inflation, exchange rate, financial leverage, operating leverage and company liquidity simultaneously have a significant effect to share investment risk on the food and beverage industry in indonesia stock exchange period 2013-2017 and the variable of exchange rate with financial leverage variable have a negative and significant effect to share investment risk on the food and beverage industry in indonesia stock exchange period 2013-2017.